Mechanism of MRX inhibition by Rif2 at telomeres - Roisné-Hamelin, Florian; Pobiega, Sabrina; Jézéquel, Kévin; Miron, Simona; Dépagne, Jordane; Veaute, Xavier; Busso, Didier; Du, Marie-Hélène Le; Callebaut, Isabelle; Charbonnier, Jean-Baptiste; Cuniasse, Philippe; Zinn-Justin, Sophie; et al. (Nature communications, 2021)
Specific proteins present at telomeres ensure chromosome end stability, in large part through unknown mechanisms. In this work, we address how the Saccharomyces cerevisiae ORC-related Rif2 protein protects telomere. We show that the small N-terminal Rif2 BAT motif ( B locks A ddition of T elomeres) previously known to limit telomere elongation and Tel1 activity is also sufficient to block NHEJ and 5’ end resection. The BAT motif inhibits the ability of the Mre11-Rad50-Xrs2 complex (MRX) to capture DNA ends. It acts through a direct contact with Rad50 ATP-binding Head domains. Through genetic approaches guided by structural predictions, we identify residues at the surface of Rad50 that are essential for the interaction with Rif2 and its inhibition. Finally, a docking model predicts how BAT binding could specifically destabilise the DNA-bound state of the MRX complex. From these results, we propose that when an MRX complex approaches a telomere, the Rif2 BAT motif binds MRX Head in its ATP-bound resting state. This antagonises MRX transition to its DNA-bound state, and favours a rapid return to the ATP-bound state. Unable to stably capture the telomere end, the MRX complex cannot proceed with the subsequent steps of NHEJ, Tel1-activation and 5’ resection. Different proteins localised at telomeres ensure chromosome end stability to prevent double strand-end break recognition. Here the authors provide new insight into how in S. cerevisiae the interaction between Rif2 and Rad50 inhibits MRX functions at telomeres.